Trends in Invasive Pneumococcal Disease in Cancer Patients After the Introduction of 7-valent Pneumococcal Conjugate Vaccine: A 20-year Longitudinal Study at a Major Urban Cancer Center. (17th August 2017) - Lee, Yeon Joo; Huang, Yao-Ting; Kim, Seong Jin; Kerpelev, Marina; Gonzalez, Victoria; Kaltsas, Anna; Papanicolaou, Genovefa
Abstract : IPD incidence declined in children aged 1–4 years and in adults with hematologic malignancies "after PCV7." The decline was abrupt in 2000 and sustained throughout 2010. The decline of IPD in adults suggests an indirect effect of PCV7. Abstract: Background: Rates of invasive pneumococcal disease (IPD) declined since routine childhood immunization with the 7-valent pneumococcal conjugate vaccine (PCV7) in 2000. We studied the impact of PCV7 on the incidence of IPD in cancer patients. Methods: This was a retrospective analysis of adult and pediatric patients treated at Memorial Sloan Kettering Cancer Center from 1992 to 2012. Recovery of Streptococcus pneumoniae from a sterile site defined IPD. IPD incidence was calculated as cases per 1, 000 unique patient-visits per year (UPV). IPD incidence was calculated for the periods: "before PCV7" (1992–2000), "after PCV7" (2001–2010) and "after PCV13" (2011–2012). Results: Of 343 IPD cases, 165, 155, and 23 cases occurred "before PCV7, " "after PCV7" and "after PCV13" respectively. The IPD incidence declined from 0.43 "before PCV7" to 0.17 "after PCV7" (95% confidence interval [CI]: 0.33–0.46, P < .001) and 0.11 "after PCV13" (95% CI: 0.42–0.96, P = .004). Adults with hematologic malignancies and children had the highest incidence. In patients 1–4 years old, the incidence declined from 11.2 "before PCV7" to 2.38 "after PCV7" (79% decrease, 95% CI: 0.1–0.4, P < .001). In patients with hematologic malignancies, the incidence declined from 2.55 "before PCV7" to 0.92 "after PCV7" (64% decrease, 95% CI: 0.27–0.47, P < .001). Conclusions: The incidence of IPD among cancer patients sharply declined after introduction of PCV7; especially in high risk groups. The decline in adults suggests an indirect effect from PCV7 childhood vaccination.